(untitled) (Religious dialogue and cooperation, 2022)
The term religion is in fact a complete system of ideas, beliefs andvalues,while religiosity implies a subjective or personal attitude, which usually occurs withthe adoption of a particular religious belief. Religion as a broader termmorereflectsthe global, socio-cultural aspect, while religiosity refers more to the individual, iehisindividual aspect. As a social phenomenon, religiosity is notavailable to our perception,because it is part of the inner side of man. As a subtle category that touches thedeepestlayers of the human being, religiosity is most expedient to be examined withindicatorsthat, given their multiplicity, impose theneed for their grouping. In our research, areusedindicators that cover the four components of religiosity. Namely: Indicators that refertothe cognitive- emotional component, ie the belief in the supernatural being as well asthe feelings that the individual builds up towards the supernatural being; Indicators thatrefer to the conative component, ie the behavior of the individual that arises fromthebelief and emotions; The indicators that refer to the action component, ie that coverthepractice, ie. performing religious rites; As well as the indicators related to the knowledgeofthe theological doctrine of one’s own religion. We should point out that in this researchweused the term “classical” religiosity, a term that is taken as used by all important researchersin our area. The allegations and analyzes presented in this text are based onthedataobtained from the research conducted in the ohrid-struga region, a region whichwithitsspecifics as a multicultural and multi-confessional environment covers the municipalitiesof Ohrid, Struga, Vevcani and Debrca. In this research, we started fromthe assumptionthat religiosity is correlated with the following socio- demographic characteristics, suchas: confessional affiliation, gender, age, place of residence town-village, marital status,level of education and social status. This paper will present some of the results oftheresearch that refer to only one segment, ie the religiosity of the population intheohrid-struga region in terms of belief depending on socio-demographic characteristics.